Insights Into Nitric Oxide Modulated Quorum Sensing Pathways - Heckler, Ilana; Boon, Elizabeth M. (Frontiers in Microbiology, 2019)
The emerging threat of drug resistant bacteria has prompted the investigation into bacterial signaling pathways responsible for pathogenesis. One such mechanism by which bacteria regulate their physiology during infection of a host is through a process known as quorum sensing. Bacteria use quorum sensing to regulate community-wide gene expression in response to changes in population density. In order to sense these changes in population density, bacteria produce, secrete and detect small molecules called autoinducers. The most common signals detected by Gram-negative and Gram-positive bacteria are acylated homoserine lactones and autoinducing peptides, respectively. However, increasing evidence has supported a role for the small molecule nitric oxide (NO) in influencing quorum sensing-mediated group behaviors like bioluminescence, biofilm production, and virulence. In this review, we discuss three bacteria that have an established role for NO in influencing bacterial physiology through quorum sensing circuits. In two Vibrio species, NO has been shown to affect quorum sensing pathways upon coordination of hemoprotein sensors. Further, NO has been demonstrated to serve a protective role against staphylococcal pneumonia through S-nitrosylation of a quorum sensing regulator of virulence.